Big Tech Financial Rollercoaster: GAFAM's 2022 Performance Review - Michal GOLINSKI (Communications of International Proceedings, 2023)
The technology giants, Google, Apple, Meta, Amazon and Microsoft, referred to as GAFAM, have become key actors in the digital economy. As digital platforms, they operate high up the value chain, generating huge revenues and profits and occupying leading positions in terms of market value. However, in 2022, symptoms of a GAFAM crisis emerged.  This phenomenon has not yet been sufficiently explained in the research literature. This paper aims at filling this gap and investigating the scale and causes of the collapse. The study is based on an analysis of official financial statements of the companies in question and it uses financial portals. The paper proposes probable causes of the phenomenon described. The analysis carried out reveals that the weakening of GAFAM in 2022 was, however, temporary as the situation improved significantly in 2023, with GAFAM’s financial results closer to those from before the crisis. An attempt to foretell the future of these companies is also presented
Keywords: GAFAM; digital economy; digital platforms; digital destruction